Hardiness, Social Support, and Academic Stress of Students Working on Bachelor’s Thesis during the Pandemic - Mukhammad Febriyano Handara; Diana Tien Irafahmi (Universitas Ahmad Dahlan, 2022)
One of the mandatory requirements for obtaining a bachelor's degree is completing a bachelor's thesis. The current COVID-19 pandemic, on the other hand, creates several pressures that cause students to fall behind on their thesis completion. This study aimed to determine how hardiness and social support affect students' ability to cope with academic stress while writing their bachelor’s thesis during a pandemic. A 5-point Likert scale questionnaire was used to collect the data. The total research sample consisted of 207 students from a public university in Indonesia working on their thesis during the pandemic. Multiple linear regression analysis was used to analyze the data. This study found that hardiness and social support all significantly negatively impact academic stress. The greater the students' hardiness and social support, the less academic stress they will experience. The findings also show that the primary source of stress for students writing their thesis is a lack of academic support, which has implications for the need to design a suitable support system mechanism so that thesis writing can be completed on time.